‘Asoulity’ as Translation of Anattā: Absence, not Negation - Sugunasiri, Suwanda H. J. (Canadian Journal of Buddhist Studies, 2011)
This paper seeks how best to capture in English the Buddha’s concept of anattā. First, the Brahmanic concepts of anātman and ātman are contrasted with the concepts of anattā and attā in Buddhism. Pointing out that the prefix a- in anattā is used by the Buddha in the sense of ‘absence’ rather than ‘negation’, the term ‘asoulity’ is proposed as best capturing the sense of the term, in the contexts of both sentience and dhammā (phenomena). In a theoretical thrust, distinguishing between anātman 1 and 2 in Brahmanism and attā 1 and 2 in Buddhism, a linguistic concept, zero-seme is introduced. The autonomous nervous system that responds to stimuli without an inherent centre is posited as an analogy of anattā.,